HUBUNGAN ANTARA KEMAMPUAN DASAR DAN PENGEMBANGAN KARIR DENGAN PRODUKTIVITAS KERJA PT MERLIN BANDUNG - Fauziah, Neneng (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2015)
Connection between basic capacity and developing of career with productivity work labour at PT Merling Bandung.This research as a purpose to know as far as possible bussines to select labour based on basic capacity and how long a bussines developing of career to increase work labour productivity. From this research results were found that; (1) there is a connection between basic capacity with work productivities; (2) there is a connection between developing of career with work productivities; (3) there is a connection developing of career in a together with work productivities.